Infant feeding and HIV for Eastern and Southern Africa, 1999-2001 - UNICEF Eastern and Southern African Region (2001)
This compilation of materials aims to enhance its users' understandi ng and knowledge of the complexity of factors influencing infant feedin g for HIV positive mothers, and the programmes to optimize the health o f the mother and the child and to reduce mother to child transmission.
compiled by Marlou Bijlsma
System requiremts: Adobe Acrobat reader
Keywords: AIDS (Disease) in infants -- Prevention; Breastfeeding -- Health aspects; HIV Infections -- transmission; Infants -- Nutrition